Meningkatkan Literasi Studi Islam dalam Memberdayaan Masyarakat Melalui Friday Literacy - Akbar, Nashr; Jazil, Thuba; Wijaya, Rusdiana Priyatna; Effendi, Erus (Tazkia Islamic University College, 2025)
Community service is a concept and practice where individuals, groups, or institutions make a positive contribution to society in a sustainable manner. The goal of this service is to improve the quality of life, address social issues, and support sustainable development. One form of this service is through educational development by conducting studies of classical Islamic texts in the Friday Literacy program. Classical Islamic texts refer to traditional Islamic literature that covers various religious aspects such as religious knowledge, fiqh (Islamic law), tafsir (Qur'anic exegesis), hadith (traditions of Prophet Muhammad), aqidah (beliefs), and others. Studying these texts can have a significant positive impact on the Muslim community, including enhancing understanding of Islamic teachings, strengthening faith, and improving religious practices. In the Friday Literacy program for the 2023/2024 period, the focus of the study is directed towards the book Ihya Ulumuddin by Imam Al-Ghazali and understanding of waqf (endowment). Ihya Ulumuddin is one of the monumental works in Islamic literature that covers various aspects of spirituality and Islamic ethics. Through this study, it is hoped that the community can gain a deeper understanding of Islamic values and the importance of waqf in community empowerment and socio-economic development.